Warming Causes Atypical Phenology in a Univoltine Moth With Differentially Sensitive Larval Stages - Poitou, Laura; Laparie, Mathieu; Pincebourde, Sylvain; Rousselet, Jérôme; Suppo, Christelle; Robinet, Christelle (Frontiers in Ecology and Evolution, 2022)
Climate change profoundly alters the phenology of insects, yet the mechanisms at play remain particularly elusive for univoltine species. Those species typically have to deal with contrasting thermal conditions across their development and life stages occurring at different seasons may have different thermal sensitivity. A modelling framework taking into account stage-specific thermal biology is lacking to predict the effect of climate change on the phenology of such species. Insect development rate scales non-linearly with temperature. This can be described with a thermal performance curve within each developmental stage, enabling higher accuracy near developmental thresholds than linear degree-day models. This approach, however, requires ample data to be correctly estimated. We developed a phenological model based on stage-specific performance curves to predict the phenology of a univoltine species undergoing uninterrupted larval development from summer to next spring, the pine processionary moth (Thaumetopoea pityocampa). This gregarious species is an important pine defoliator and is known to readily respond to climate change with a consistent and sustained range expansion/shift since the 1990s, as winter warming facilitates its survival in previously unsuitable areas. First, we determined the thermal performance curve of development rate for each stage from the egg to the fourth larval instar by monitoring moulting in larval colonies exposed to fluctuating thermal treatments in controlled conditions. Second, we developed a phenology model to simulate the cumulated development rate across successive life stages, using observation data of adult flights and daily mean temperatures as input variables. A good fit was found between predictions and observations. Finally, the model was used to explore phenological consequences of hypothetical climate variations. With a simulated increase of temperature by 3 °C, the model successfully predicted atypical ends of larval development before winter, which are being observed in nature in some regions or during years with autumnal heatwaves. With a simulated heatwave, carry-over effect on life stages development were predicted. On this winter-active species, we illustrate how variations in development rate caused by climate variations in early development can feedback into subsequent stages typically developing slowly in the cold season, and ultimately snowball into more significant phenological changes.